The spirit-eaters - Hunter, Erin (Hunter, Erin. Bravelands, 2020)
The baboon Thorn rises as the new Great Father and tries to unite all the animals of the Bravelands but a pack of rogue wolves target the Great Herd forcing Sky to choose between duty and family. Meanwhile, Fearless searches for Titan and suspects the wolves know information about the lion. It is time for the Great Herd to come together to defend the wild from an ancient evil that is taking root.